Effect of pyrolytic carbon interface on the properties of 3D C/ZrC–SiC composites fabricated by reactive melt infiltration. Issue 8 (June 2016) - Wang, Dengke; Dong, Shaoming; Zhou, Haijun; Kan, Yanmei; Wang, Zhen; Zhu, Guangxiang; Chen, Xiaowu; Cao, Yanpeng
Abstract: 3D C/ZrC–SiC composites have been fabricated by slurry infiltration combined with reaction melt infiltration method. In order to clarify the effect of fiber/matrix (F/M) interface on properties on 3D C/ZrC–SiC, pyrocarbon (PyC) interface with various thickness (160–1100 nm) was introduced by chemical vapor infiltration. The microstructure, mechanical properties and ablation properties were investigated systematically. Results showed that thicker PyC could protect fiber bundles from the erosion caused by the melt, leading to the as-prepared 3D C/ZrC–SiC with more excellent mechanical properties. The flexural strength and fracture toughness of C/ZrC–SiC composites with 850 nm PyC was 125.67±2.49 MPa and 4.82±0.48 MPa m 1/2, respectively, which obtained 181% and 81% improvement compared with that of C/ZrC–SiC with 160 nm PyC. However, as the thickness of PyC rised from 850 nm to 1100 nm, mechanical properties of C/ZrC–SiC decreased obviously. Also, after the ablation test, it was found that C/ZrC–SiC with 470 nm PyC showed the best ablation resistance as SiC content was improved and porosity was lower in contrast with that of other composites.